ALIGNING MAQASHID SHARIAH AND COMMUNITY-BASED TOURISM: A CASE STUDY OF PAHAWANG'S TOURISM MODEL - Al-Kahfi, Muhammad Fakhri; Fadila , Nisa Rahma (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study explores the implementation of Community-Based Halal Tourism (CBHT) in Pahawang Tourism Village by integratig the principles of Maqashid Shariah to address the gaps in existing halal tourism frameworks, such as the Global Muslim Travel Index (GMTI). While GMTI focuses on practical elements like halal food availability, prayer facilities, and Muslim-friendly services, it lacks a deeper ethical and spiritual dimension. Maqashid Sharia which includes preserving religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-aql), lineage (hifz al-nasl), and wealth (hifz al-mal) enhances halal tourism by promoting sustainability, ethical practices, and community welfare. Using a qualitative approach, this research collects primary data through interviews and observations in the field, supported by secondary data from relevant literature. The findings demonstrate that CBHT in Pahawang prioritizes community involvement, providing halal based services such as accommodations, worship facilities, and local crafts while maintaining environmental and cultural sustainability. Additionally, Maqashid Shariah fosters social responsibility through zakat distribution, which supports education, infrastructure, and equitable income distribution. This study highlights the research gap where conventional halal tourism indicators emphasize traveler needs but neglect holistic Islamic principles. By applying Maqashid Shariah, CBHT offers a comprehensive model that aligns tourism practices with ethical and spiritual values, ensuring longterm sustainability and community empowerment thus provides a valuable case study for integrating Islamic ethics into tourism management.